Tudbulul. [anthology].
The story tells about a mythological hero, lived alone with his family in a forest site called Lemhadong. One day, he organized a concert in which he gathered all the known musical instruments and played them one after the others with his sisters. It attracted many inhabitants of the forest, who were delighted and decided to stay and live together with Tudbulul: this is how was founded the Tboli nation.
Found in: Philippine Folk Literature: The Epics. (GR 325 P48 2001 v.8)
Keywords: Literature-Collections.